Examining polarizing and non-polarizing filters for road sports - Mercatelli, Luca (Frontiers in Sports and Active Living, 2023)
The use of sunglasses and polarized sunglasses is common in all aspects of life and is very popular in outdoor athletic activities. However, the choice of athletes regarding their sunglasses is often not dictated by the performance ensured by one model rather than another but by other factors such as look or wearability due also to the lack of technical data on cataloguess. A conscious choice of filters to use, also according to road and weather conditions, supported by quantitative data, would instead allow athletes to improve their visual comfort and sport experience. The transmission spectra of 10 pairs of sports sunglasses (five polarized and five not polarized) were measured and related to the road luminance for different sun positions in both horizontal and vertical polarizations. The luminous transmission factor was calculated, and the luminance quantities while wearing the glasses were defined and calculated for all cases. A survey was submitted to a group of athletes to collect their impressions and relate them to the measurement results. The pairs of polarized and non-polarized sports sunglasses showed similar transmission factors, so their ability to mitigate outdoor light is almost the same—the main difference lies in the polarized light transmitted. Outdoor measurements showed that the light reflected by the road has a substantial polarized horizontal component. Polarized sunglasses block much of the light reflected by the road, resulting in a darker appearance of the road and reducing the glare of the scene in bright sunlight. The decrease in road luminance increases the contrast discrimination of other objects in the scene, which reflect sunlight in a non-polarized way (e.g., non-flat surfaces). The survey demonstrates that interviewed athletes prefer polarized sunglasses for these aformentioned reasons. This study highlights the advantages of polarizing sunglasses for athletic activities on roads because the road surface often reflects polarized light depending on the position of the sun.